Effect of Trichoderma Addition on Sargassum Organic Fertilizer. Issue 1 (March 2021) - Kusumawati, R; Nurhayati; Pangestu, H E; Basmal, J
Abstract: Trichoderma is a fungus that can function as decomposers, biological agents, and stimulators of plant growth, bio fungicides so that agricultural plants can avoid diseases caused by poisonous fungi. This fungus can live in media containing seaweed by breaking down the seaweed's carbohydrate macromolecules into simple sugars. Sargassum seaweed is now starting to be used as raw material for organic fertilizers and Trichoderma can be added to a certain amount of organic fertilizer formulations to produce biological fertilizers. For this reason, this study aims to find the best time to obtain the highest density of Trichoderma in organic fertilizer Sargassum and its characteristics. The highest density of Trichoderma in Sargassum SLF which received additional silage was obtained on the 21st day namely 1.3×10 6 cfu/mL, whereas in Sargassum SLF without silage on the 7th day namely 46×10 6 cfu/mL. Based on the comparison of chemical parameters between Sargassum SLF without silage and commercial SLF, it was known that Sargassum SLF was better in terms of c-organic content, macronutrients (P and K), and minerals (Na, Mg, S, Fe, Mn, Cu, Zn, B, Al, Cd, and Mo).